Identification of criteria affecting software project monitoring task of Agile Kanban method - Alaidaros, Hamzah; Omar, Mazni; Romli, Rohaida (IP Publishing LLC, 2018)
Currently, software development organizations (SDOs) attempt to deliver their software products quickly, within the prescribed period, and with the highest quality and lowest cost, yet this is proven a big challenge for them. Agile Kanban method recently is gaining increasing attention and popularity, due to its numerous advantages that make it performs better than other methods in terms of managing software projects. Beside of that, it has a board that used to visualize the workflow and monitor the project progress. However, various studies have shown that this method has significant challenges that negatively impact the scheduling of the development process. Consequently, late delivery of software projects may occur, thus the rate of projects’ failures will be increased. This paper aims to identify the challenges and criteria that affect the progress monitoring task of Agile Kanban method using a narrative review method, whereby this review method is adopted to identify and summarize what has been previously published, avoid duplications, and seek new study areas which are not yet addressed. Finally, the findings of this study would be used to develop an improved software project monitoring task model of Agile Kanban method. That model would be capable to keep projects progress as it is planned, and thus leading to successful delivering for software projects according to its specifications, time, and budget.